2011
DOI: 10.1163/157075511x597584
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites reveal weak genetic differentiation between Rutilus frisii kutum (Kamenskii, 1901) populations south of the Caspian Sea

Abstract: Rutilus frisii kutum (Kamenskii, 1901) is one of the most important bony fish inhabiting the Caspian Sea. The Iranian Fisheries Organization produced up to 200 million fry to restock the Caspian Sea population annually. Loss of genetic stocks and gradual depletion of the gene pool are parameters of great concern for the future of the species. In the present study, we used ten microsatellite markers to estimate the level of genetic diversity and compare the degree of genetic differentiation among kutum populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In addition to the mentioned possible reasons, microsatellites are more efficient to detect genetic variation in species than RFLP (Shaw, Turan, Wright, O'Connell, &Carvalho, 1999), which may explain the lower concordance among the RFLP data and our results. However, our results were in accordance to the study by Rezaei et al (2011) who reported the number of alleles, expected and observed heterozygosity 8.29, 0.793 and 0.766, respectively for three wild populations (Goharbaran, Tajan and Qaresou) of Caspian kutum using the same microsatellite loci. While the observed and expected heterozygosity noticed in the present study were higher than those reported in 13 other freshwater (H O : 0.46 and H E : 0.54) and 7 anadromous species (H O and H E : 0.68), the mean number of alleles was lower than that of freshwater and anadromous fishes (9.1 and 10.8, respectively) (DeWoody&Avise, 2000).…”
Section: Discussion Analysis Of Population Genetic Variationsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition to the mentioned possible reasons, microsatellites are more efficient to detect genetic variation in species than RFLP (Shaw, Turan, Wright, O'Connell, &Carvalho, 1999), which may explain the lower concordance among the RFLP data and our results. However, our results were in accordance to the study by Rezaei et al (2011) who reported the number of alleles, expected and observed heterozygosity 8.29, 0.793 and 0.766, respectively for three wild populations (Goharbaran, Tajan and Qaresou) of Caspian kutum using the same microsatellite loci. While the observed and expected heterozygosity noticed in the present study were higher than those reported in 13 other freshwater (H O : 0.46 and H E : 0.54) and 7 anadromous species (H O and H E : 0.68), the mean number of alleles was lower than that of freshwater and anadromous fishes (9.1 and 10.8, respectively) (DeWoody&Avise, 2000).…”
Section: Discussion Analysis Of Population Genetic Variationsupporting
confidence: 93%
“…However, as reported by Balloux and Lugon-Moulin (2002), even this low level of F ST may indicate important genetic differentiation. The low F ST value was previously detected between the other wild populations of R. kutum (Rezaei et al, 2011) whereas Rezvani-Gilkolaei et al (2012) reported a moderate level of genetic differentiation between the southwest populations of Caspian kutum, possibly related to the difference in geographical localities of sampling. Sefc, Payne, and Sorenson (2007) demonstrated that because of greater variance, R ST is less dependable for detecting differentiation than F ST .…”
Section: Genetic Relationship and Differentiation Among Populationsmentioning
confidence: 79%
See 3 more Smart Citations